Pendampingan Asesmen Minat dan Bakat Siswa SMA Imanuel Kalasan dalam Menghadapi Disrupsi Teknologi - Wiranata, F. Edwin; Putri, Indah Sepwina; Christina, Mikha Meilinda (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2024)
The development of Artificial Intelligence (AI) technology and other disruptions require students and workers to be adaptive to global needs. Students, in particular, must be prepared to develop themselves to remain relevant and become human resources that compete in the increasingly technologically advanced world of work and industry. These self-development efforts cannot be separated from recognizing an individual's personality, character, and temperament (PKT) to discover their interests and talents. Currently, one of the assessment tools for PKT that experts in the field have developed is Karaktera. This community service is carried out at SMA Immanuel Kalasan, which has students with various backgrounds and currently needs help understanding the character of each student better. Using Karaktera, the service team carries out a PKT assessment by starting and ending with material relevant to technological disruption and developing interests and talents. As a result, the school and students felt very helpful in recognizing individual character and being aware of self-development to become quality human resources.